2007
DOI: 10.1007/s11423-007-9034-9
|View full text |Cite
|
Sign up to set email alerts
|

Learners’ perceptions of instructional design practice in a situated learning activity

Abstract: This case study investigated learners' perceptions of value from participating in a learning activity designed to model professional instructional design practice. Learners developed instructional design products for a corporate client in the context of a classroom-based course. The findings indicate that learners perceived different kinds of value which varied according to the degree of integration of learners' goals with client's goals, ranging from (a) co-constituted value (in which learners perceived the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Research involving social learning theory and placing students in authentic learning environments has been recently conducted involving language acquisition, community building, engineering writing, pedagogy of teacher education, art curriculum for K‐5 students, and corporate business applications (Comas‐Quinn et al., ; Edmonds‐Cady & Sosulski, ; Johri & Olds, ; Korthagen, ; Pitri, ; Wasko & Faraji, ; Woolf & Quinn, ). The consensus between these research projects is students are able to develop a deeper understanding of content when one is involved in its real‐world application rather than formal learning in school, which is often not transferred as one might wish.…”
Section: Theoretical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Research involving social learning theory and placing students in authentic learning environments has been recently conducted involving language acquisition, community building, engineering writing, pedagogy of teacher education, art curriculum for K‐5 students, and corporate business applications (Comas‐Quinn et al., ; Edmonds‐Cady & Sosulski, ; Johri & Olds, ; Korthagen, ; Pitri, ; Wasko & Faraji, ; Woolf & Quinn, ). The consensus between these research projects is students are able to develop a deeper understanding of content when one is involved in its real‐world application rather than formal learning in school, which is often not transferred as one might wish.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…The consensus between these research projects is students are able to develop a deeper understanding of content when one is involved in its real‐world application rather than formal learning in school, which is often not transferred as one might wish. Scaffolding also appeared as an important part of teaching students in this manner, as instructors initially helped students and promoted community but eventually stepped back allowing the pupils to take full charge of their activity (Edmonds‐Cady & Sosulski, ; Johri & Olds, ; Woolf & Quinn, ). By applying situated learning theory to educational practices, students collaborate in groups (Comas‐Quinn et al., ; Edmonds‐Cady & Sosulski, ; Johri & Olds, ; Korthagen, ; Mills, ; Paretti, ; Pitri, ; Shaltry, Henriksen, Wu, & Dickson, ); engage with people in community, which teaches them how to interact in professional settings (Edmonds‐Cady & Sosulski, ; Johri & Olds, ; Korthagen, ; Shaltry et al., ; Woolf & Quinn, ); and work through real‐life challenges (Comas‐Quinn et al., ; Edmonds‐Cady & Sosulski, ; Johri & Olds, ; Korthagen, ; Mills, ; Shaltry et al., ).…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Multiple authors have indicated the relevance of cases in ID education (Choi and Lee, 2008; Jonassen, 1999, 2011; Jonassen and Hernandez-Serrano, 2002; Woolf and Quinn, 2009). In this study, where participants took part in several educational activities such as peer-reviews, discussions, small group presentations, or instructional projects, results indicate that case studies analysis was perceived by the participants as the most valuable learning experience in the course.…”
Section: Discussionmentioning
confidence: 99%
“…Though teaching presence is a major area for research in blended learning, there are still divergences as to its effect on student academic performance (Almasi & Zhu, 2017;Vo, Zhu, & Diep, 2017;Thomas, 2018;Kwak, Menezes, & Sherwood, 2014). Research shows that how learners perceive a learning activity cannot be predicted in advance (Petraglia, 1998a(Petraglia, , 1998b cited in Woolf & Quinn (2009). Consequently, it cannot be assumed that learners will perceive the value of an activity as intended by course designers (Woolf & Quinn, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that how learners perceive a learning activity cannot be predicted in advance (Petraglia, 1998a(Petraglia, , 1998b cited in Woolf & Quinn (2009). Consequently, it cannot be assumed that learners will perceive the value of an activity as intended by course designers (Woolf & Quinn, 2009). Still, other researchers have echoed that instructors "perception of what teaching is and what role they think they play has influence on the way they teach (Morgan, 2011;2018a).…”
Section: Introductionmentioning
confidence: 99%